Biological responses to rapid climate change at the Younger Dryas-Holocene transition at Krakenes, western Norway - Birks, HJB; Birks, HH (SAGE PUBLICATIONS LTD, 2008)
A fine-resolution pollen-stratigraphical study, supported by macrofossil analysis, has been made at Krakenes Lake, western Norway through the Younger Dryas-Holocene transition and the early Holocene. The median sample-age difference is 14 cal. yr for the period 9175-11 625 cal. yr BP. The chronology is based on 57 AMS radiocarbon dates. The pollen stratigraphy is interpreted as a primary succession following deglaciation at the end of the Younger Dryas. Palynological richness, compositional turnover and rates of assemblage change are estimated from the pollen-stratigraphical data. Comparisons between palynological turnover at Krakenes and floristic turnover on recently deglaciated modern glacier forelands suggest a comparable primary succession and turnover at Krakenes. However, the arrival and expansion of Betula pubescens (tree birch) was delayed by about 450 years. Possible reasons for this lag are discussed. Comparisons between turnover estimates for pollen and for diatoms through the Younger Dryas-Holocene transition highlight differences in the response dynamics of terrestrial and aquatic ecosystems at Krakenes Lake. This fine-resolution study links the long temporal perspective provided by palaeoecology with the fine temporal scales of modern ecological observations. The primary succession following rapid climate warming at Krakenes provides a context for other past and present responses to climate warming and it can provide a long-term perspective on responses to projected future climate warming.